Engineering model of dielectric strength in phase‐to‐phase air gaps. Issue 19 (23rd July 2020) - Gao, Jiachen; Wang, Linong; Lian, Zhangxiang; Li, Guanlin; Fang, Yaqi; Song, Bin
Abstract : Phase‐to‐phase air gap is a type of external insulation in power transmission and transformation projects. The dielectric strength of phase‐to‐phase air gaps affects the safety and reliability of power systems. Currently, in the external insulation design of power transmission and transformation projects, discharge tests are mainly used to obtain the dielectric strength of air gaps. Due to the lack of reasonable prediction model of dielectric strength, the design of the tests is not reasonable enough, which are time consuming and costly. In order to solve the problem, an engineering model of dielectric strength in phase‐to‐phase air gaps was proposed in this study. The engineering model could predict the dielectric strength in phase‐to‐phase air gaps by finite‐element method simulation and numerical calculation. In this study, the engineering model was applied in ultra high voltage (UHV) substations and UHV compact transmission lines to predict the dielectric strength of tubular busbar phase‐to‐phase air gaps and conductor phase‐to‐phase air gaps. The predicted results were in good agreement with discharge test results, and the errors were <6%, which proved the engineering model has certain applicability in power transmission and transformation projects.